Profissionalidade docente em projetos de cursos de Pedagogia de Universidades do Estado de Goiás - BIANCO, Rita de Cássia R. Del (2009)
This bibliographic research, related to the Teaching Formation and Professionalization research line of the Education Graduate Program of Universidade Federal de Goiás, analyzes Pedagogy Course Projects of public and private Universities in the state of Goiás, namely: Universidade Católica de Goiás UCG (private); Universidade Federal de Goiás UFG (public) and Universidade Estadual de Goiás UEG (public). Considering historical, political and social contexts, the caracteristics of each course's projects, of brazilian education from late 70's to the present time, as well as the qualitative aspects of the investigated reality, metodologically, we guide our study through the dialetic method. In this sense, the first chapter talks about concepts and conjectures inherent to the teaching profession, professionality and knowledge. Educational legislation and political view of each institution constitute founding elements for project dimensioning, and also for formation and understanding of historical and material characteristics that permeate the teaching profession. In the second chapter we discuss about Higher Education in Goiás, taking into account the researched institutions. In the third chapter, we elaborate the anaysis of Course Projects aiming to make a connection with theoretical references from the first chapter. Finally, we conclude that teaching professionality presents itself in the historical and temporal contradiction, sometimes as polical or ethical, on other times focused on pragmatism, but always requiring constant confrontation and reviewing while facing the historical devir present in the educational field.